Kes [videorecording (DVD)] - Loach, Ken, 1936- (Criterion collection ;, 2011)
Billy Casper, a 15-year-old working class Yorkshire boy, is a scrappy loner who delivers papers before and after school, shares a bed with his bullying brother, Jud, and mostly ignores his self-absorbed mother. His routine is derailed when he spots a small falcon, a kestrel, in the countryside. He's raised birds in the past and is inspired to capture a young kestrel and try his hand at falconry. When not enduring the scorn of his peers and "betters," Billy wanders the countryside, pokes about the town, and secretively trains his kestrel, where his intelligence and imagination are as free as the bird. Because ever present in Billy's mind is fear and hatred of the pit--the local mine where he is destined to spend his adult life digging coal.